An application of coincidence degree theory to cyclic feedback type systems associated with nonlinear differential operators - Feltrin, Guglielmo; Zanolin, Fabio (Topological Methods in Nonlinear Analysis, 2017)
Using Mawhin’s coincidence degree theory, we obtain some new continuation theorems which are designed to have as a natural application the study of the periodic problem for cyclic feedback type systems. We also discuss some examples of vector ordinary differential equations with a φ-Laplacian operator where our results can be applied. Our main contribution in this direction is to obtain a continuation theorem for the periodic problem associated with (φ(u’))’ + λ k(t,u,u’) = 0, under the only assumption that φ is a homeomorphism.